The REPowerEU Plan and the Transition to Green Energy in Romania - Violeta Mihaela Dinca; Simona Moagar-Poladian; Tanase Stamule; Puiu Nistoreanu (Amfiteatru Economic, 2023)
The energy system of the European Union has suffered major changes in the recent years. High energy prices, increased energy security concerns and heavy reliance on gas, oil, and main combustibles coming from Russia have the three most important features of the EU energy sector in 2022. The European Commission has presented in the first part of 2022 the REPowerEU Plan which aims to implement measures to economise energy, generate clean energy, and diversify the origin of energy provisions and stocks. This program is supported by economic and legislative actions to shape the additional energy infrastructure and framework that Europe requires. This article focuses on the part related to the green energy transition of the REPowerEU, by investigating the perception of Romanian companies about favourably substituting fossil fuel to decrease emissions and reliance. This research examined the obstacles/challenges that have an impact on the adoption of renewable energy from the point of view of Romanian companies. An econometric model was conceived and it encompassed five variables that were analysed to see how they could impact the decision to accept and implement green energy in Romania. The article applied a quantitative study, with the primary data collected with a survey on managers in companies from five of the most energy intensive industries in Romania. The data was processed with the structural equation modelling (SEM) and the results revealed that market (economic), technological and administrative obstacles affect with a major impact the implementation of renewable energy technologies in Romania. Community (social) and organisational obstacles have been determined to influence with a medium effect on the deployment of renewable energy technologies in Romania. The outcomes of the article contribute to increasing awareness of the imperativeness of substituting fossil fuels by accelerating Romania s clean energy transition and considering the great potential the country has for making this switch.
Keywords: Q40; R15; M14; 330; REPowerEU Plan; renewable energy transition; substitution of fossil fuels; Romanian companies